Association between Virulence Factors and TRAF1/4-1BB/Bcl-xL Expression in Gastric Mucosa Infected with Helicobacter pylori - Fen Wang; Xiang Wu; Zhiying Liu; Guangkui Bu; Xiayu Li; Nanfang Qu; Jin Peng; Canxia Xu; Shourong Shen; Yi Yuan (Gastroenterology Research and Practice)
Objective. CagA+/vacAs1+/vacAm1+ Helicobacter pylori upregulates the expression of tumor necrosis factor receptor–associated factor 1 (TRAF1), tumor necrosis factor receptor superfamily member 9 (4-1BB), and B-cell lymphoma-extra large (Bcl-xL) in human gastric epithelial cells. We investigated the correlation between cagA/vacAs1/vacAm1 and TRAF1/4-1BB/Bcl-xL expression in gastric mucosal tissue of patients with gastric disorders. Methods. We collected gastric mucosa samples from 35 chronic, nonatrophic gastritis (CG) patients, 41 atrophic gastritis patients, 44 intestinal metaplasia with atypical hyperplasia (IM) patients, and 28 gastric carcinoma (Ca) patients. The expression of  TRAF1, 4-1BB, and Bcl-xL was determined using western blotting. The expression of cagA, vacAs1, and vacAm1 in H. pylori was examined with polymerase chain reaction. Results. The expression of TRAF1, 4-1BB, and Bcl-xL was significantly upregulated in IM and Ca patients (P<0.05 compared with CG). There were more cases of cagA+/vacAs1+/vacAm1+ H. pylori infection in samples with elevated TRAF1, 4-1BB, or Bcl-xL expression (P<0.05). Additionally, there were a remarkably large number of samples with upregulated TRAF1/4-1BB/Bcl-xL expression in cases of cagA+/vacAs1+/vacAm1+ H. pylori infection (44 cases, 67.7%; P<0.05). Conclusions. The pathogenesis of IM and Ca may be promoted by cagA+/vacAs1+/vacAm1+ H. pylori, possibly via upregulated TRAF1, 4-1BB, and Bcl-xL in gastric mucosal tissue.